Evaluación de trastornos músculo esqueléticos de origen radicular en miembros superiores mediante la aplicación de técnicas neurodinámicas de diagnóstico, en los trabajadores de “Inlog S. A” de la ciudad de Guayaquil. - Zurita Avilés, Gabriel Sebastián (2019)
Musculoskeletal disorders are very common and are one of the highest causes of injuries and work absences, making the affectations or compressions to the nerve roots that are present one of the main consequences that have been presented. Repetitive moves and lifting loads without any type of physical preparation or correct use of biomechanics are the main causes of this disorder. The main objective of this investigation is to evaluate musculoskeletal disorders of radicular origin in the upper limbs of the body through the application of neurodynamic diagnostic techniques on "Inlog S. To" workers in the Guayas canton during the period of November 2018 through March 2019. The methodological approach used is quantitative, not experimental. Neurodynamic tests were used to evaluate the musculoskeletal disorders with radicular origin as an occupational risk to which 100 workers were exposed to. The percentage of workers with musculoskeletal injuries was 81%, for that reason we developed a guide of diagnostic neurodynamic techniques, for upper limbs, directed to the Catholic University Santiago de Guayaquil, Faculty of Medical Sciences and Physical Therapy.